Fluid transport with suspended particles by means of dilating peristaltic waves - Pandey S.K.; Tiwari S.K. (My University, 2025)
In the present study, transport of a Newtonian fluid containing uniformly distributed tiny particles moving in a cylindrical tube is investigated when the peristaltic wave amplitude dilates exponentially. Long wavelength approximation is used to get rid of non-linear inertia terms. It is observed that dilation of wave-amplitude during propagation enhances pressure but reduces it with rising concentration of particulate suspension. Pressure rises with the amplitude dilation parameter in case solid particles are suspended in the fluid. Pressure is also observed to increase in the distal part of the tube. © 2020, Springer Nature Switzerland AG.